Association Between Coffee Consumption and Gastroesophageal Reflux Disease (GERD): A Cross-Sectional Analysis - Hartoyo, Farrell ZR; Tandarto, Kevin; Sidharta, Veronika; Tenggara, Riki (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Gastroesophageal reflux disease (GERD) is a condition in which stomach contents flow back into the esophagus, leading to various symptoms and complications. In Indonesia, the prevalence of GERD has been reported at 57.6%. Coffee consumption is often suspected to be closely linked to the occurrence of GERD. This study aims to determine the association between coffee consumption and the incidence of GERD.Methods: This study used a cross-sectional approach to conduct observational analytical research. The sample included individuals aged 18 to 65 years residing in Jakarta, selected using a consecutive sampling method. Data were collected using the Indonesian version of the Gastroesophageal Reflux Disease Questionnaire (GERD-Q). To assess the association between coffee consumption and GERD, the Chi-square test of independence was applied.Results: Out of 105 respondents, 26 were identified as having GERD. Among those, 84.6% reported consuming coffee at moderate to high frequencies, while 15.3% consumed little to no coffee. The Chi-square test of independence revealed a statistically significant association between coffee consumption and GERD among Jakarta residents aged 18 to 65 years (p = 0.006).Conclusion: There is a significant association between coffee consumption and the incidence of gastroesophageal reflux disease (GERD) among Jakarta residents aged 18 to 65 years.